Influência de Interface sobre as propriedades Ferroicas e Multiferroicas de Nanoestruturas de Pb(Zr0,2Ti0,8)O3/CoFe2O4 Crescidas via RF-Sputtering - Bonini, Ricardo Pereira (Universidade Federal de São Carlos, 2023)
This work shows a systematic study of the structural, microstructural, ferroic and multiferroic coupling properties of bilayer thin films of the PZT/CFO system, with the constituent phases varying in thickness from 20 to 300 nanometers. These heterostructures were fabricated by physical deposition using the radio frequency sputtering technique (RF-Sputtering). Through the structural study, it was possible to determine the lattice parameters of each constituent phase of the heterostructures and, in this way, quantitatively determine the strain remaining in each layer of the films and evaluate its evolution as a function of the thickness of the layers. In this work it was also possible to study the ferroelectric and ferromagnetic properties and to correlate these properties with the thickness and the strain and determine their influence on these properties. In this regard, it was possible to determine how the ferroic properties can influence the multiferroic coupling between the constituent phases of the heterostructure, as well as the role that the interface has on this coupling.
Influence of Interface on the Ferroic and Multiferroic Properties of Nanostructures Pb(Zr0.2Ti0.8)O3/CoFe2O4 Grown via RF-Sputtering
Keywords: Filme fino; Heteroestruturas multiferroicas; Acoplamento magnetoelétrico; Acoplamento magnetodielétrico; Strain; Stress; CIENCIAS EXATAS E DA TERRA::FISICA